Structure and chemical bonds in reactively sputtered black Ti–C–N–O thin films - Chappé, J. M. (2011)
The evolution of the nanoscale structure and the chemical bonds formed in Ti–C–N–O films grown by reactive sputtering were studied as a function of the composition of the reactive atmosphere by increasing the partial pressure of an O2+N2 gas mixture from 0 up to 0.4 Pa, while that of acetylene (carbon source) was constant. The amorphisation of the films observed by transmission electron microscopy was confirmed by micro- Raman spectroscopy, but it was not the only effect associated to the increase of the O2+N2 partial pressure. The chemical environment of titanium and carbon, analysed by X-ray photoemission spectroscopy, also changes due to the higher affinity of Ti towards oxygen and nitrogen than to carbon. This gives rise to the appearance of amorphous carbon coexisting with poorly crystallized titanium oxynitride. The evolution of the films colour is explained on the basis of these structural changes.